2017
DOI: 10.3727/154427217x15094520591330
|View full text |Cite
|
Sign up to set email alerts
|

Tapping the Chinese Market: an Examination of Chinese Tourists' Images and Constraints Towards Cruising

Abstract: This study examined Chinese tourists' images and constraints towards cruising, and their influences on cruising desires/intentions. Both qualitative and quantitative methodologies were utilized. Based on an extensive literature review, semistructured interviews were conducted to determine measurement items for constructs of interest. Quantitative data were then collected in order to examine the proposed hypotheses. An innovative procedure for developing the best items to be included in the scales was utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…As the only identified Chinese cruise constraint paper in the Chinese academic literature, this source corroborates Dong and Chick (), who found that respondents in six major Chinese cities cited time and money as the biggest constraints to overall leisure activity. The importance of time constraints, corroborating Kerstetter et al () as well as Hung and Petrick () in their U.S.‐based investigations (see Table ), was not evident in a more recent convenience sample of 309 Chinese adults collected from the international departure lounge of Guangzhou airport and from consumers who had requested information about overseas travel from two Chinese travel agencies (Zou & Petrick, , ). Rather, the not‐an‐option item of preference for other travel alternatives was the most important constraint, followed by the three structural items of insufficient cruise information, expense (no income threshold was imposed on this sample), and immaturity of the Chinese ocean cruise industry.…”
Section: Literature Reviewsupporting
confidence: 57%
See 4 more Smart Citations
“…As the only identified Chinese cruise constraint paper in the Chinese academic literature, this source corroborates Dong and Chick (), who found that respondents in six major Chinese cities cited time and money as the biggest constraints to overall leisure activity. The importance of time constraints, corroborating Kerstetter et al () as well as Hung and Petrick () in their U.S.‐based investigations (see Table ), was not evident in a more recent convenience sample of 309 Chinese adults collected from the international departure lounge of Guangzhou airport and from consumers who had requested information about overseas travel from two Chinese travel agencies (Zou & Petrick, , ). Rather, the not‐an‐option item of preference for other travel alternatives was the most important constraint, followed by the three structural items of insufficient cruise information, expense (no income threshold was imposed on this sample), and immaturity of the Chinese ocean cruise industry.…”
Section: Literature Reviewsupporting
confidence: 57%
“…Also reflecting the latter, the statement “I heard bad news about ocean cruising” was added to reflect social and conventional media coverage of negative cruise and ferry experiences, and “I cannot afford it” was substituted for “too expensive” to reflect preferred wording of the affordability dimension. That the item from Zou and Petrick (, ) concerning the immaturity of the domestic ocean cruise industry did not appear in the open‐ended responses may at least in part reflect the rapid development of that sector in the 3‐year data collection interval between those and the current study. The final version of the questionnaire can be seen in the Appendix.…”
Section: Methodsmentioning
confidence: 69%
See 3 more Smart Citations